A non‐chemical weed control strategy, introducing duckweed into the paddy field. Issue 8 (10th June 2022) - Wang, Feng; Wang, Shuang; Xu, Shuhan; Shen, Jianying; Cao, Linkui; Sha, Zhimin; Chu, Qingnan
Abstract: BACKGROUND: Herbicide resistance in weeds and environmental pollution resulting from excessive application of chemical herbicides keeps increasing. Development of environment‐friendly and effective weed management strategies are required for sustainable agricultural production. In this study we investigated the effects of duckweeds ( Landoltia punctata (G. Meyer) Les & D. J. Crawford and Spirodela polyrhiza (Linnaeus) Schle iden) introduction on the weed community and rice growth in paddy fields. RESULTS: The study was conducted in the two rice‐growing seasons (2018 and 2019) with three treatments: rice grown without duckweed introduction (CK), with L. punctata introduction (LP), and with S. polyrhiza introduction (SP). On average, LP and SP significantly reduced total weed density by more than 90% and 97%, respectively. Early in the rice‐growing season, both duckweed species completely prevented weed growth. Further, both species significantly promoted rice plant growth in the advanced stages. SP significantly improved grain yield of rice by 23%. Light transmittance, temperature of the floodwater and soil, floodwater pH, and dissolved oxygen content significantly decreased following introduction of the duckweeds, indicating that the duckweeds introduction might inhibit weeds growth by altering environmental factors. CONCLUSION: This study provides a possible environment‐friendly way to inhibit weed biomass in the paddy field by introducing duckweeds and interpreted the possible reasons of the impacts of duckweed on environmental variables. Weed control is beneficial for rice growth. Duckweed coverage might be limited in open fields and the associated practice requires additional investigation. © 2022 Society of Chemical Industry. Abstract : This study confirmed weed control, rice growth promotion, and environmental effects of two duckweed species ( Landoltia punctata and Spirodela polyrhiza ) introduction in paddy field.